To solve the inequality \( x - \frac{1}{3} \leq \frac{1}{2} \), we can follow these steps:
- Isolate \( x \): Add \( \frac{1}{3} \) to both sides of the inequality.
\[ x \leq \frac{1}{2} + \frac{1}{3} \]
- Find a common denominator: The common denominator for 2 and 3 is 6.
\[ \frac{1}{2} = \frac{3}{6}, \quad \frac{1}{3} = \frac{2}{6} \]
- Add the fractions:
\[ \frac{3}{6} + \frac{2}{6} = \frac{5}{6} \]
- Write the final result:
\[ x \leq \frac{5}{6} \]
The solution to the inequality is:
\( x \leq \frac{5}{6} \), which corresponds to the second response option provided:
\( x \text{ less-than-or-equal-to } \frac{5}{6} \).